2012
DOI: 10.5194/hess-16-3405-2012
|View full text |Cite
|
Sign up to set email alerts
|

It takes a community to raise a hydrologist: the Modular Curriculum for Hydrologic Advancement (MOCHA)

Abstract: Abstract. Protection from hydrological extremes and the sustainable supply of hydrological services in the presence of changing climate and lifestyles as well as rocketing population pressure in many parts of the world are the defining societal challenges for hydrology in the 21st century. A review of the existing literature shows that these challenges and their educational consequences for hydrology were foreseeable and were even predicted by some. However, surveys of the current educational basis for hydrolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 58 publications
0
55
0
Order By: Relevance
“…Hydrologists are working in a field which is becoming increasingly interdisciplinary and therefore requires better communication with non‐hydrologists (Wagener et al ., ). Students with proper training in uncertainty analysis will have a toolkit to scrutinise modelling efforts and thereby contribute to decision‐making processes with substantiated claims of knowledge or lack thereof.…”
Section: Seven Reasons To Be Positive About Uncertainty Estimationmentioning
confidence: 97%
“…Hydrologists are working in a field which is becoming increasingly interdisciplinary and therefore requires better communication with non‐hydrologists (Wagener et al ., ). Students with proper training in uncertainty analysis will have a toolkit to scrutinise modelling efforts and thereby contribute to decision‐making processes with substantiated claims of knowledge or lack thereof.…”
Section: Seven Reasons To Be Positive About Uncertainty Estimationmentioning
confidence: 97%
“…Observations of the water cycle tend to focus on one aspect of the water cycle and seldom offer a complete description. For example, we can estimate total terrestrial water storage (Wahr, 2004) or the top 5 cm surface soil moisture via multiple satellite missions. It is difficult, however, to directly combine such observations of components of the water cycle into a complete picture of the water cycle.…”
Section: Challenges and Opportunities For DL In Hydrologymentioning
confidence: 99%
“…Recent research has shown a potential for great variability within the hydrological curriculum (Wagener et al, 2012). This variability includes differences in not only what conceptual material should be taught (Gleeson et al, 2012) but also how this material should be delivered pedagogically (Wagener, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that an emerging requirement for new hydrological engineers is the ability to not only develop a well-defined knowledge base of basic hydrological concepts but also synthesize this conceptual learning with more authentic "real-world" knowledge gained from the interpretation and application of this knowledge (Merwade and Ruddell, 2012). Unfortunately, field and modeling activities are often lacking in the hydrological curriculum, at least at the undergraduate and lower-division level (ASCE, 1990;MacDonald, 1993;Nash et al, 1990;Ruddell and Wagener, 2013;Wagener et al, 2007Wagener et al, , 2012. This is especially concerning as, unlike laboratory sciences such as physics and chemistry, hydrology is fundamentally a place-based science.…”
Section: Introductionmentioning
confidence: 99%